Impact of opportunistic salpingectomy on anti‐Müllerian hormone in patients undergoing laparoscopic hysterectomy: a multicentre randomised controlled trial. (24th June 2016) - Song, T; Kim, MK; Kim, M‐L; Jung, YW; Yun, BS; Seong, SJ; Kwon, S‐H
Abstract : Objective: The aim of the study was to investigate whether opportunistic salpingectomy has any deleterious effects on ovarian reserve and increases surgical risk in patients undergoing laparoscopic hysterectomy. Design: A multicentre, randomised controlled trial. Setting: Three university hospitals in Korea. Population: Sixty‐eight patients undergoing laparoscopic hysterectomy for the treatment of symptomatic benign uterine diseases. Methods: Patients were randomised to undergo either opportunistic salpingectomy ( n = 34) or no salpingectomy ( n = 34) during laparoscopic hysterectomy. Main outcome measurements: The primary and secondary outcome measures were the change of ovarian reserve, determined by the rate of decline in anti‐Müllerian hormone (AMH) level from before surgery to 3 months post‐surgery and surgical outcomes, respectively. Results: Baseline demographic and clinical characteristics were similar between the two groups. There was also no difference in operative outcomes such as operative time, operative bleeding, or complications between the two groups. In both groups, postoperative AMH levels were significantly lower than preoperative AMH levels (both, P < 0.01). The decline rate in AMH was 12.5% (interquartile range 0.8–60.9%) in the opportunistic salpingectomy group and 10.8% (interquartile range 6.9–27.4%) in the no salpingectomy group, with no significant difference between both groups ( P = 0.898). Conclusions: Opportunistic salpingectomy at the time of laparoscopic hysterectomy did not have any negative effects on ovarian reserve or increased surgical risk. Tweetable abstract: Opportunistic salpingectomy did not have any negative effects on ovarian reserve or increased surgical risk. Tweetable abstract: Opportunistic salpingectomy did not have any negative effects on ovarian reserve or increased surgical risk.